2011
DOI: 10.1037/a0025259
|View full text |Cite
|
Sign up to set email alerts
|

Depleted parental psychological resources as mediators of the association of income with adherence and metabolic control.

Abstract: For adolescents with type 1 diabetes, lower family income may be associated with poorer diabetes management through depleted parental psychological resources (i.e., higher parental depressive symptoms, lower parental acceptance). Adolescents (n=252; 46% male) aged 10-14 years with type 1 diabetes assessed the acceptance of their mother and father (e.g., gives me the feeling that she likes me as I am; she doesn't feel she has to make me over into someone else). Mothers provided information on family income and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…For example, there is the possibility that IQ is simply a proxy for other factors, such as socio-economic status (SES; Taylor, Frier, Gold, &Deary, 2003), which itself is an important predictor of diabetes care. For example, children with type 1 diabetes from lower SES households have poorer glycemic control, more hospitalizations, and more hypoglycemic episodes (Drew, Berg, King, Verdant, Butler, Griffiths, & Wiebe, 2011). However, studies investigating the roles of both IQ and factors related to SES found that IQ is a unique correlate of health outcomes and disease knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is the possibility that IQ is simply a proxy for other factors, such as socio-economic status (SES; Taylor, Frier, Gold, &Deary, 2003), which itself is an important predictor of diabetes care. For example, children with type 1 diabetes from lower SES households have poorer glycemic control, more hospitalizations, and more hypoglycemic episodes (Drew, Berg, King, Verdant, Butler, Griffiths, & Wiebe, 2011). However, studies investigating the roles of both IQ and factors related to SES found that IQ is a unique correlate of health outcomes and disease knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, for example, the relationship between low income and glycemic control was explained by lower levels of parental acceptance [63]. Parents of minority youth have also demonstrated lower levels of monitoring than parents of white youth [22].…”
Section: Factors Affecting Parental Involvementmentioning
confidence: 99%
“…In a sample of 81 adolescents with T1D and their parents, Botello-Harbaum and colleagues [13] found that over a 12-month period, parental responsiveness continued to promote greater self-reported quality of life in their child. On the other hand, Drew et al [14] showed depleted family resources – emotional as well as financial – were associated with poorer metabolic control among 252 adolescents with T1D. Maintaining the daily routines necessary for diabetes management was less successful in families with lower parental acceptance (communication of love, warmth, acceptance) and higher levels of parental depressive symptoms, especially when there was the added stress of low family income.…”
Section: Introductionmentioning
confidence: 99%